2021
DOI: 10.3390/ani11030596
|View full text |Cite
|
Sign up to set email alerts
|

Physical, Chemical and Histological Characterization of Pectoralis major Muscle of Broilers Affected by Wooden Breast Myopathy

Abstract: This study aimed to characterize the effects of wooden breast myopathy (WBM) on quality of broiler chicken breast meat. Normal samples (absence of myopathy), moderate-degree samples (hardness only in one area of the breast fillet) and severe-degree samples (hardness throughout the breast fillet) were classified. In macroscopic analysis, the pectoral muscle affected by the WBM showed, in general, pale color with stiff, irregular and reddish regions (suffusions and petechiae), with the presence of white striatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 49 publications
4
11
1
Order By: Relevance
“…According to our analyses, an increase of 1 mm in fillet thickness or of 1 cm of fillet width was associated with a respective increase of 17% and 37% of the odds for the fillets to develop a myopathy. These results are in line with reports from the literature, which show that increased width and thickness in the cranial part of the pectoralis major muscle were associated with increased likelihood that this muscle would switch from normal to myopathic, and have higher BMM severity scores (Griffin et al 2018;Oliveira et al 2021;Che et al 2022b).…”
Section: Discussionsupporting
confidence: 92%
“…According to our analyses, an increase of 1 mm in fillet thickness or of 1 cm of fillet width was associated with a respective increase of 17% and 37% of the odds for the fillets to develop a myopathy. These results are in line with reports from the literature, which show that increased width and thickness in the cranial part of the pectoralis major muscle were associated with increased likelihood that this muscle would switch from normal to myopathic, and have higher BMM severity scores (Griffin et al 2018;Oliveira et al 2021;Che et al 2022b).…”
Section: Discussionsupporting
confidence: 92%
“…In broiler chickens, myofibers of muscle pectoralis contain perimysium consisting of dense connective tissue that collects muscle fibers in bundles (fascicles) [ 52 ]. In our work, we found that the pectoral muscle bundles of domestic ducks were surrounded by perimysium and endomysium which consisted of less dense connective tissue relative to cattle egrets.…”
Section: Discussionmentioning
confidence: 99%
“…Injuries such as the wooden breast condition bring potential disadvantages to consumer acceptance and purchase intent of poultry meat. Wooden breast myopathy is characterized by accentuated hardness on palpation of the breast, production of mucous exudate, petechiae, and white stripes, as well as areas with separate muscle bundles, particularly within the deep layers of the muscle ( Oliveira et al, 2021b ). Those injuries not only negatively affect the visual characteristics of the breast but also decrease the yield of the product during processing, which also results in economic loss.…”
Section: Introductionmentioning
confidence: 99%